Cadtest winning over practices. (Architects' Journal, 2003)
Provides information on Cadtest, the benchmarking system for measuring and monitoring computer-aided design performance. Number of organizations that have signed up to use Cadtest; List of architectural firms that availed of the services of Cadtest.